2021
DOI: 10.1111/coep.12529
|View full text |Cite
|
Sign up to set email alerts
|

Rules of origin and trade preference utilization among least developed countries

Abstract: This article assesses how the utilization of trade agreements responds to rules of origin revisions that allow for more foreign content in exported products. Using the revision of the rules of origin for apparel products under the European Union's generalized system of preferences as a case study, and a triple‐difference empirical framework, the results indicate that rules of origin act as a significant bottleneck to least developed countries' (LDCs) use of trade preferences. However, heterogeneity in the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…These factors include the preference erosion[14] that stems from both the greater liberalization [15] of most favoured nations (MFN) tariffs (in particular since the creation of the WTO) and the end of multi-bre agreement (e.g., Inama, 2003;Klasen et al, 2021;Low et al, 2009;Persson, 2015b); domestic economic policies, including trade policies [16] and the real exchange rate policies [17]; the limited supply response capacity of bene ciary countries (e.g., Gradeva and Martínez-Zarzoso 2016;Low et al, 2009;Prowse, 2010;Yannopoulos, 1986Yannopoulos, , 1987; the inadequate product coverage (e.g., Low et al, 2009;Persson, 2015b); the existence of restrictive rules of origin as well as other compliance costs by the bene ciary countries when claiming a NRTP (e.g., Brenton and Özden 2009;Gitli, 1995;Persson, 2015b;WTO, 2019); and the lack of certainty or stability of the improved market access brought about by the NRTP (e.g., Hakobyan, 2020;Persson, 2015b). For example, concerning the rules of origin, the literature has shown that restrictive 'preferential' rules of origin can constrain the bene ts of tariff preference margins (e.g., Cadot et al, 2014) by leading to a misallocation of resources (e.g., Falvey and Reed, 1998;Mattoo et al, 2003) and ultimately undermining the utilization of NRTPs (Hakobyan, 2015;Herz and Wagner, 2011;Inama, 2003;Sytsma, 2021;WTO, 2019). WTO (2019) has explored the rationale for the low rates of preference utilization for several agricultural exports under many NRTPs, despite the simple feature of agricultural products, and the fact that these products are subject to simple rules of origin.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…These factors include the preference erosion[14] that stems from both the greater liberalization [15] of most favoured nations (MFN) tariffs (in particular since the creation of the WTO) and the end of multi-bre agreement (e.g., Inama, 2003;Klasen et al, 2021;Low et al, 2009;Persson, 2015b); domestic economic policies, including trade policies [16] and the real exchange rate policies [17]; the limited supply response capacity of bene ciary countries (e.g., Gradeva and Martínez-Zarzoso 2016;Low et al, 2009;Prowse, 2010;Yannopoulos, 1986Yannopoulos, , 1987; the inadequate product coverage (e.g., Low et al, 2009;Persson, 2015b); the existence of restrictive rules of origin as well as other compliance costs by the bene ciary countries when claiming a NRTP (e.g., Brenton and Özden 2009;Gitli, 1995;Persson, 2015b;WTO, 2019); and the lack of certainty or stability of the improved market access brought about by the NRTP (e.g., Hakobyan, 2020;Persson, 2015b). For example, concerning the rules of origin, the literature has shown that restrictive 'preferential' rules of origin can constrain the bene ts of tariff preference margins (e.g., Cadot et al, 2014) by leading to a misallocation of resources (e.g., Falvey and Reed, 1998;Mattoo et al, 2003) and ultimately undermining the utilization of NRTPs (Hakobyan, 2015;Herz and Wagner, 2011;Inama, 2003;Sytsma, 2021;WTO, 2019). WTO (2019) has explored the rationale for the low rates of preference utilization for several agricultural exports under many NRTPs, despite the simple feature of agricultural products, and the fact that these products are subject to simple rules of origin.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…For supporting evidence on non-reciprocal ROO see de Melo and Portugal-Perez (2014) for AGOA and Brunelin et al (2019) for Jordan's exports to the EU and US. For EBA, see and Sytsma (2021a).…”
Section: Firm-level Evidencementioning
confidence: 99%
“…Restrictive preferential rules of origin can constrain the bene ts of tariff preference margins (e.g., Cadot et al, 2014b) and more generally, deter[27] exports, and undermines the utilization of NRTPs (Hakobyan, 2015;Inama, 2003;Sytsma, 2021;WTO, 2019). Building on the case of Vietnam, Doan and Xing (2018) have demonstrated that lenient rules of origin improve countries' export e ciency, de ned as the ratio of actual exports to the maximum possible volume.…”
Section: Issue Of Preferential Rules Of Originmentioning
confidence: 99%
“…[22] Rules of origin specify the minimum level of local transformation (i.e., the amount of local content or processing) required to make manufactured products eligible for preferential tariff treatment (e.g., Cadot et al, 2006;Sytsma, 2021).…”
Section: Issue Of Preferential Rules Of Originmentioning
confidence: 99%